Evaluation of the Efficiency of Transfer Processes in a Rotary Apparatus - A. M. Volk; A. I. Vilkotsky; O. N. Pyzhcova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
This paper considers the possibility of using vortex devices for interphase interaction while carrying out various physical and chemical processes in the chemical, food, gas production, construction and other industries. In the processes of mass transfer, one or several distributed components perform the transition from one phase to another through the active surface of their interface. To perform the implementation of these processes in absorbers, rectifiers, adsorbers, extractors effectively, the developed surface of the interacting phases acquire s a particular significance. Most of the chemical reactions in reaction devices and heterogeneous media occur when the initial distributed substances are supplied to the reaction zone and when the resulting products are removed from the chemical interaction zone through the phase interface. The processes under consideration are also used in solving environmental problems, viz. for sanitary cleaning of ventilation gases, wet cleaning of emissions. During evaporation, absorption, rectification, wet cleaning of gases and other processes, the problem of preventing the entrainment of liquid droplets with the gas flow is of great importance. One of the designs of a rotary multistage mass transfer apparatus is considered which makes it possible to achieve a finely dispersed liquid spray, uniform in height, with an ascending cross-flow of gas. The diagrams of installations for carrying out the experiment are given. On the basis of experimental studies, the dependence of the average diameter of dispersed liquid droplets on the geometric and hydrodynamic parameters has been obtained. The dispersed composition is described and dependences are given for determining the main characteristics used in physicochemical processes. The theoretical calculation of the movement of particles of the dispersed phase in the working volume of the apparatus at different flow rates of liquid and gas has been carried out. Theoretical and experimental methods were used to estimate the carryover of the liquid phase, an analysis of the process was carried out, and practical recommendations were given.